Evidence for Higgs boson decay to a pair of muons; Journal of High Energy Physics; Vol. 2021, iss. 1 - Sirunyan A. M.; Tumasyan A. R.; Adam W. Wolfgang; Babaev A. A. Anton Anatoljevich; Yuzhakov A. D. Aleksandr Dmitrievich; Sukhikh L. G. Leonid Grigorievich; Okhotnikov V. V. Vitaly Vladimirovich (2021, 2021)
Title screen